Rho3 of Saccharomyces cerevisiae, Which Regulates the Actin Cytoskeleton and Exocytosis, Is a GTPase Which Interacts with Myo2 and Exo70 - Robinson, Nicole G. G. (American Society for Microbiology, 1999)
The Rho3 protein plays a critical role in the budding yeast Saccharomyces cerevisiae by directing proper cell growth. Rho3 appears to influence cell growth by regulating polarized secretion and the actin cytoskeleton, since rho3 mutants exhibit large rounded cells with an aberrant actin cytoskeleton. To gain insights into how Rho3 influences these events, we have carried out a yeast two-hybrid screen using an S. cerevisiae cDNA library to identify proteins interacting with Rho3. Two proteins, Exo70 and Myo2, were identified in this screen. Interactions with these two proteins are greatly reduced or abolished when mutations are introduced into the Rho3 effector domain. In addition, a type of mutation known to produce dominant negative mutants of Rho proteins abolished the interaction with both of these proteins. In contrast, Rho3 did not interact with protein kinase C (Pkc1), an effector of another Rho family protein, Rho1, nor did Rho1 interact with Exo70 or Myo2. Rho3 did interact with Bni1, another effector of Rho1, but less efficiently than with Rho1. The interaction between Rho3 and Exo70 and between Rho3 and Myo2 was also demonstrated with purified proteins. The interaction between Exo70 and Rho3 in vitro was dependent on the presence of GTP, since Rho3 complexed with guanosine 5′-O-(3-thiotriphosphate) interacted more efficiently with Exo70 than Rho3 complexed with guanosine 5′-O-(3-thiodiphosphate). Overlapping subcellular localization of the Rho3 and Exo70 proteins was demonstrated by indirect immunofluorescence. In addition, patterns of localization of both Exo70 and Rho3 were altered when a dominant active allele of RHO3, RHO3(E129,A131), which causes a morphological abnormality, was expressed. These results provide a direct molecular basis for the action of Rho3 on exocytosis and the actin cytoskeleton.